Histone Methyltransferase EZH2: A Potential Therapeutic Target for Kidney Diseases - Li, Tingting; Yu, Chao; Zhuang, Shougang (Frontiers in Physiology, 2021)
Enhancer of zeste homolog 2 (EZH2) is a histone-lysine N-methyltransferase enzyme that catalyzes the addition of methyl groups to histone H3 at lysine 27, leading to gene silencing. Mutation or over-expression of EZH2 has been linked to many cancers including renal carcinoma. Recent studies have shown that EZH2 expression and activity are also increased in several animal models of kidney injury, such as acute kidney injury (AKI), renal fibrosis, diabetic nephropathy, lupus nephritis, and renal transplantation rejection. The pharmacological and/or genetic inhibition of EZH2 can alleviate AKI, renal fibrosis and lupus nephritis, but potentiate podocyte injury in animal models, suggesting that the functional role of EZH2 varies with renal cell type and disease model. In this article, we summarize the role of EZH2 in the pathology of renal injury and relevant mechanisms and highlight EZH2 as a potential therapeutic target for kidney diseases.